SDG4 - Quality education : inclusivity, equity and lifelong learning for all - Ferguson, Therese; Iliško, Dzintra; Roofe, Carmel; Hill, Susan (Concise guides to the United Nations Sustainable Development Goals ;, 2019)
SDG4 - Quality Education: Inclusivity, Equity and Lifelong Learning For Allwill explore the multifaceted and complex nature of the concepts of inclusivity and quality education.